Program Bedah Rumah BAZNAS dan Dampaknya terhadap Kualitas Hidup Masyarakat Duafa di Kabupaten Sambas - Deni Irawan (Jurnal Ilmiah Al-Muttaqin, 2025)
The house renovation (Bedah Rumah) program implemented by BAZNAS of Sambas Regency is a strategic effort to improve the quality of life of the poor (Duafa) through the provision of decent and healthy housing. The research problem arises from the inadequate housing conditions of Duafa communities as well as challenges related to funding limitations and institutional coordination in program implementation. This study aims to evaluate the effectiveness of the BAZNAS Sambas Regency house renovation program in improving beneficiaries’ quality of life, to identify challenges in program implementation, and to analyze the collaboration between BAZNAS Sambas Regency and Zakat Collection Units (UPZ) in Sambas District. The research method employed is a descriptive qualitative approach using in-depth interviews with beneficiaries and relevant stakeholders. The results indicate that the house renovation program has successfully improved housing quality, social welfare, health, and the living environment of beneficiaries. However, the program still faces challenges related to limited funding and suboptimal coordination with UPZ. Nevertheless, collaborative efforts among institutions have gradually shown positive progress. This study recommends strengthening institutional collaboration, increasing funding support, and expanding program coverage to reach a broader population of Duafa.